Nutrition—sensitive agricultural interventions and maternal and child nutrition outcomes in arid and semi—arid lands of Kenya - Grant, Frederick K. E.; Amunga, Dorcas; Mulwa, Chalmers K.; Moyo, Mukani; Kwikiriza, Norman; Malit, Jack; Mwaura, Lucy; Maru, Joyce; Heck, Simon (Frontiers in Nutrition, 2025)
BackgroundIn regions facing chronic stress such as the arid and semi-arid lands (ASALs) of Kenya, there is poor quality of diet among women and children in humanitarian situations, mainly due to multiple climatic shocks that exacerbate local food systems. The objective of this study was to assess the effect of household participation in climate smart nutrition-sensitive agriculture (NSA) interventions on maternal and young child nutrition outcomes in Makueni, Garissa and Tana River counties.MethodsFrom March 2020 to October 2023, the International Potato Center and partners (World Food Program, Ministries of Agriculture and Health) implemented an NSA intervention in Makueni, Garissa and Tana River counties. The intervention comprised of household participating in three main activities: (1) access to orange fleshed sweetpotato (OFSP) vines; (2) participation in nutrition education activities and (3) receiving and utilizing infant feeding toolkits (Healthy Baby Toolkit/HBT). Approximately 3 months after intervention activities, we conducted a cross-sectional survey in intervention communities to assess effect of particpation in the interventions on maternal and child nutrition outcomes. The study utilized the doubly robust inverse probability weighting regression adjustment (IPWRA) estimator to evaluate the impact of participation in the project intervention on nutrition outcomes. Caregivers’ knowledge of nutrition, health and childcare, women (MDD-W) and young child dietary diversity (MDD-C), vitamin A (VA) intakes, minimum meal frequency (MMF), and minimum acceptable diet (MAD) for children 6–23 months were analyzed. The comparison of means and proportions was assessed using Student’s t-test and the Chi-square test, respectively, between the caregivers participating in NSA interventions and non-participants. The impact of the level of participation in NSA interventions and information on how to utilize these to improve infant and maternal feeding in the household on caregiver knowledge and practices scores was examined using regression analysis.ResultsOf 494 caregivers surveyed, 72% indicated to have participated in at least one study intervention. In adjusted analyses, participation in at least one of the study interventions was significantly associated with improved caregiver nutrition [β: 0.943, p < 0.05], and VA [0.613, p < 0.05] knowledge scores and young child MMF [0.202, p < 0.05] and MAD [0.111, p < 0.05]. Participation in all three interventions (nutrition training, use of infant feeding toolkit and access to OFSP vines) significantly increased VA knowledge among caregivers (p ≤ 0.05) and infant MMF (p ≤ 0.05). While the use of infant feeding toolkit and access to OFSP vines alone had a significant positive effect on MDD-W and MDD-C (p ≤ 0.05).ConclusionThe findings show the need to integrate climate-smart NSA interventions in humanitarian settings to improve nutrition among women and young children. Such interventions can potentially build resilience among populations in these fragile environments to better withstand various shocks.